Perubahan Spasial Wilayah Permukiman Muslim Sekumpul Terkait Aktivitas Dakwah KH Muhammad Zaini Abdul Ghani - Muhamad Ratodi; Arfiani Syariah (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
Ulama have taken an important role in the people of South Kalimantan, not only in terms of social cohesion but also in the forerunner of Muslim settlements. Taking the case in Sekumpul Martapura, This study tries to identify the development pattern of the Sekumpul settlement delineation due to KH Muhammad Zaini Abdul Ghani's da'wah activities, and identification of changes in the function of the area. The settlement delineation spatial-sprawl obtained by Google Earth and Geospatial Information Agency and supported by structured interviews with key informants using a snowball sampling technique. The results showed the expression of spatial delineation development in the Sekumpul area run naturally and adapted what looks like an octopus pattern with the road network as its dominant factor. In the 1980s until recently the Sekumpul area has experienced three times changes in its function, from the center of propagation, residential, into economic functions with its religious tourism concept. There were no specific guidelines found in the da'wah material regarding the technical aspects of spatial development. One important message conveyed by KH Muhammad Zaini Abdul Ghani was to uphold the rights of guests. This concept was then very tightly held by the residents of Sekumpul, which impacted on the maximum provision of facilities and infrastructure for the pilgrims.